2017
DOI: 10.1016/j.dental.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of grape seed extract in polylactide microcapsules for sustained bioactivity and time-dependent release in dental material applications

Abstract: Objective To sustain the bioactivity of proanthocyanidins-rich plant-derived extracts via encapsulation within biodegradable polymer microcapsules. Methods Polylactide microcapsules containing grape seed extract (GSE) were manufactured using a combination of double emulsion and solvent evaporation techniques. Microcapsule morphology, size distribution, and cross-section were examined via scanning electron microscopy. UV-vis measurements were carried out to evaluate the core loading and encapsulation efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…PLA/GSE and PLA/PEO/GSE nanofibrous membranes (around 6 mg) were dissolved in DMF/acetone (1 : 1, v/v) mixture. The actual amount of the as-loaded GSE was then quantified using UV-Vis absorption spectroscopy (Shimadzu UV-1100) by monitoring the wavelength at 280 nm against a predetermined calibration curve of the extract [30]. Neat PLA and PLA/PEO solutions using the same solvent mixture were used as blanks.…”
Section: Encapsulation Efficiency Encapsulation Efficiency (Ee)mentioning
confidence: 99%
“…PLA/GSE and PLA/PEO/GSE nanofibrous membranes (around 6 mg) were dissolved in DMF/acetone (1 : 1, v/v) mixture. The actual amount of the as-loaded GSE was then quantified using UV-Vis absorption spectroscopy (Shimadzu UV-1100) by monitoring the wavelength at 280 nm against a predetermined calibration curve of the extract [30]. Neat PLA and PLA/PEO solutions using the same solvent mixture were used as blanks.…”
Section: Encapsulation Efficiency Encapsulation Efficiency (Ee)mentioning
confidence: 99%
“…Encapsulating complex natural extract was also a challenge, and few data were reported in the literature [39][40][41]. Most authors reported the encapsulation of polyphenols extracts in various nanocarriers based on chitosan.…”
Section: Extracts Encapsulation In Alginate-based Nanocarriers 21 Phy...mentioning
confidence: 99%
“…16 While the incorporation of bioactive compounds into resinbased biomaterials sounds appealing in light of their intrinsic properties and natural character, it also may prove challenging due to stability issues (e.g., oxidation) and negative interactions with the resin chemistry. 17 Many phytochemicals are excellent antioxidants (radical scavengers expressly), which can inhibit the free-radical polymerization process. 5 Thus, the simplest way to introduce phytochemicals into acrylates, which is to disperse the active ingredient in the monomer blend, may not be reliable.…”
Section: Introductionmentioning
confidence: 99%